The lighthouse [videorecording (DVD)] - Eggers, Robert, 1983-; Dafoe, Willem; Pattinson, Robert, 1986- (Lionsgate, 2020)
A hypnotic and hallucinatory tale of two lighthouse keepers on a remote and mysterious New England island in the 1890s.